Examining The Benefits And Challenges Of Implementing Total Quality Management Practices In Manufacturing Small And Medium-Sized Enterprises In Ghana - Nyarko, Cynthia Oduro (Advances in Social Sciences Research Journal, 2021)
Micro, Small and medium-sized enterprises (MSMEs) are important to national development as they produce a huge percentage of the national output and provide an even greater proportion of employment. They play a significant role in economic growth, innovation, poverty alleviation and raise standard of living. Research has shown that most manufacturing SMEs that adopt and implement TQM practices exhibited a significant positive relationship and confirmed that TQM practices are indicators of firm performance. The study examines the benefits of TQM implementation, and the challenges these manufacturing SMEs face in their attempt to implement TQM practices. The study which was exploratory in nature used descriptive survey and a structured interview to collect data from the SMEs who were purposively selected for the interview. The study purposively selected fifty (50) owner-managers for the interview, but due to the COVID-19 health pandemic, only five (5) participated in the interview. A sample size of 5 respondents were selected for exploratory study in Accra metropolitan area of the Greater Accra region to respond to the interview instrument. The tool for qualitative data analysis was NVivo version 11. The study discovered that manufacturing SMEs adopted and implemented TQM practices in their organisations. The TQM practices which were analysed were: organisational leadership; strategic planning and development; customer focus; human resource focus; continuous improvement and process management. The study established that effective implementation of TQM practices led to financial performance of these manufacturing SMEs as there was a significant positive relationship between the TQM practices and firm performance. The study although confirmed a direct positive relationship between quality management practices and firm performance, there were numerous challenges that serves as barriers to TQM implementation in the organisations. The challenge of downsizing was the most reported among the SMEs. It is recommended that manufacturers in the SME sector must be aware of the prospects of quality management practices since the success of its implementation depends largely on its awareness. It is also recommended that SMEs identifies challenges that face its implementation of TQM, so as to eliminate any barrier to its implementation.